Quantification of exercise performance intensity during walking and running by three-dimensional accelerometry - Meamarbashi, A. (Sports Technology, 2013)
Quantification of exercise performance is crucial in the professional training of the elite athletes. Accelerometry method is the best objective, inexpensive, and non-obstructive technique for measuring physical activity. A physical activity-monitoring system (PAMS) (6 x 4 x 1.5 cm, 25 g) was designed and developed using a three-axis accelerometer with selectable measurement range (2.5?10 g). The purpose of this study was to estimate the exercise intensity and compare different instrumental methods during walking/running in the field. Randomly selected male students (n = 10) performed 2, 3, 4, 5, 6, 7, 8, and 9 km/h walking/running tests in the field for 2 min with 5-min rest in between. Physical activity during the tests was measured by the PAMS data logger, Suunto heart rate monitor, and a three-axis pedometer. The metabolic equivalent was computed by American College of Sports Medicine (ACSM), Van der Valt, and Kawahara prediction equations. A strong correlation was found between the accelerometer counts and the speed (r = 0.958). Very high correlations in all ranges of speeds were observed between ACSM equation and results of PAMS, pedometer, Suunto, Kawahara, and Van der Walt Equations (Pearson correlation coefficients: 0.968, 0.937, 0.937, 0.997, and 0.902, respectively). The accelerometer output proved to be highly reproducible and valid in different speeds. PAMS is inexpensive, precise, and light and, in contrast with commercial data loggers, has the advantages of high-speed data recording on a high-capacity memory card and feasibility of post-exercise data processing.